Analisis Produk Cacat Menggunakan Peta Kendali p - Yazid Bustommy, Abby; Edhiargo Toyosito, Rakay; Sugiarto, Emaria (Universitas Tangerang Raya, 2022)
Competition in the industrial world is very tough so that all industries are required to continue to survive by making continuous improvement. One of them in the engineering, procurement, construction (EPC) industry has a vision that is to become a company that is expected in the future and becomes an example in allocating resources owned by the oil and gas industry score. This company has many customers obtained from the tender results. This study proposes to realize, implement Occupational Health and Safety (K3) using the 5R system. Suggestions for this research and further research, namely cooperation between divisions in the company should be further improved so that consistency in doing better work and completeness of K3 in the production process also needs to be improved cooperation between divisions.